Klasifikasi gunung api aktif Indonesia, studi kasus dari beberapa letusan gunung api dalam sejarah - Pratomo, Indyo (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no4.20065Indonesia is well known as a volcanic country, where more than 30% out of all the world volcanoes occupied this region. Volcanic region is generally densely populated, because of their soil fertility and other land use. Based on their historical eruptions noted since and before 1600 A.D., the Indonesian active volcanoes are regrouped in to A type (79 volcanoes), which were defi ned as volcanoes erupted since 1600 A.D., B type (29 volcanoes) erupted before 1600 A.D., and C type (21 volcanoes) are solfatar fi elds (Bemmelen, 1949; van Padang 1951; Kusumadinata, 1979). Studies on parts of the Indonesian active volcanoes, show different eruptive characters, which are generally related to hazard potentials. A new classifi cation of Indonesian active volcanoes was proposed based on the combination of their physical properties, morphology, volcanic structure and eruptive styles to the eight differents types, those are Tambora (caldera formation), Merapi (lava dome), Agung (open crater), Papandayan (sector failure), Batur (post-caldera activities), Sangeangapi (lava fl ows) and Anak Krakatau types (volcano islands and submarine volcano). This classification would be make a better understanding to different characteristics of Indonesian active volcanoes, for the volcanic hazard and mitigation and also for the applied volcanological researches. Â